2013
DOI: 10.1098/rstb.2012.0425
|View full text |Cite
|
Sign up to set email alerts
|

Watershed responses to Amazon soya bean cropland expansion and intensification

Abstract: The expansion and intensification of soya bean agriculture in southeastern Amazonia can alter watershed hydrology and biogeochemistry by changing the land cover, water balance and nutrient inputs. Several new insights on the responses of watershed hydrology and biogeochemistry to deforestation in Mato Grosso have emerged from recent intensive field campaigns in this region. Because of reduced evapotranspiration, total water export increases threefold to fourfold in soya bean watersheds compared with forest. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 59 publications
4
85
2
2
Order By: Relevance
“…In the Brazilian Amazon, studies have found significant warming in soybean and pasture compared to forested catchments; higher temperatures were driven, in part, by reductions in riparian vegetation [Macedo et al, 2013;Neill et al, 2013]. Increased stream surface radiation from reduced shading in oil palm plantations is likely to be a contributor to these thermal dynamics [Caissie, 2006].…”
Section: Influences On Stream Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the Brazilian Amazon, studies have found significant warming in soybean and pasture compared to forested catchments; higher temperatures were driven, in part, by reductions in riparian vegetation [Macedo et al, 2013;Neill et al, 2013]. Increased stream surface radiation from reduced shading in oil palm plantations is likely to be a contributor to these thermal dynamics [Caissie, 2006].…”
Section: Influences On Stream Temperaturementioning
confidence: 99%
“…Agricultural conversion also affects stream physical and biochemical properties. For example, stream temperatures tend to be higher in agricultural than forested catchments [Macedo et al, 2013;Neill et al, 2013], while sediment concentration and load are typically elevated after land clearing [Bruijnzeel, 2004;Douglas et al, 1999]. Enhanced sediment production is often sustained through activities into recently cleared and planted oil palm (young oil palm, OPY, <3 years post clearing in 2008) and mature oil palm (OPM, >10 years).…”
Section: Introductionmentioning
confidence: 99%
“…Other papers in this Theme Issue focus on the causes and consequences of landuse change in the Brazilian state of Mato Grosso [1][2][3][4][5][6]. This article addresses an alternative question.…”
Section: Introductionmentioning
confidence: 99%
“…Durigan et al [23] Macedo et al [24] Neill et al [27] Gardner et al [42] Le Tourneau et al [41] VanWey et al [29] Schwartzman et al [34] Riskin et al [28] Stickler et al [18] Nepstad et al [47] Galford et al [30] Schiesari et al [31] Morton et al [32] Silvério et al [36] Stickler et al [18] DeFries et al [49] Schwartzman et al [34] infrastructure Nepstad et al [47] Macedo et al [24] Neill et al [27] [35] Figure 1. Schematic diagram showing the interconnections among the processes that affect land cover and land-use change (LCLUC) and the social and biophysical outcomes of LCLUC in the Brazilian Amazon.…”
Section: Land-use Change In Mato Grossomentioning
confidence: 99%
“…Forest contribution to the total evapotranspiration in MT decreased by about 20 per cent between 2000 and 2009 because of deforestation [26]. Neill et al [27] review a series of experiments testing how these changes affect stream flow in a mixed forest and soya bean landscape in MT. Catchments dominated by soya bean fields had an approximately fourfold increase in discharge compared with forested watersheds.…”
Section: (A) Land -Water Interactionsmentioning
confidence: 99%